Estruturação do programa de pré-incubação da UNIHUB Campus Foz do Iguaçu: do planejamento à operação - um modelo de apoio a iniciativas inovadoras - Oliveira, Edina Dorilda de (2025)
This paper presents the planning of the pre-incubation program at UNIHUB Campus Foz do Iguaçu, affiliated with the State University of Western Paraná (Unioeste), as well as the implementation of its Beta Phase. The research is based on the context of transformations driven by the era of innovation and technology, which have significantly expanded opportunities for youth entrepreneurship, especially in university settings. In this context, the role of incubators, and especially pre-incubators, stands out as strategic instruments for strengthening entrepreneurial culture and integrating universities, the market, government, and civil society. To support the development of the program, a Systematic Literature Review and benchmarking with technology parks in Western Paraná were conducted, focusing on preincubation models. The program was structured with the participation of both internal and external stakeholders, based on the Cerne methodology and using brainstorming to generate ideas. The result was a three-phase model: Phase A – awareness-raising and mobilization; Phase B – entrepreneurship development and development; and Phase C – project monitoring and formalization, with the cross-cutting theme of impact and purpose. The program was designed collaboratively and contextually, seeking to foster innovative entrepreneurship and serve as a benchmark for other higher education institutions interested in structuring similar initiatives.